PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA CAFE AND RESTO AZALEA - Cahyo, Alex Septian Tri; Tulhusnah, Lusiana; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2022)
Cafe is a form of informal restaurant that prioritizes the presentation of a comfortable place to relax, rest, and chat with colleagues or peers. The purpose of this study was to analyze and examine the effect of service quality and location on customer loyalty with consumer satisfaction as an intervening variable at Cafe And Resto Azalea. This research is an explanatory research. The population in this study are consumers at Cafe And Resto Azalea. The sampling technique was determined by probability sampling with simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that service quality has a significant positive effect on consumer satisfaction. Location has a significant positive effect on consumer satisfaction. Service quality has a significant positive effect on customer loyalty. Location has a positive but not significant effect on customer loyalty. Consumer satisfaction has a significant positive effect on customer loyalty. The results of the indirect effect hypothesis test show that Quality on Customer loyalty through Customer satisfaction has a significant positive effect. Location on customer loyalty through customer satisfaction has a significant positive effect.